1992
DOI: 10.2172/10122051
|View full text |Cite
|
Sign up to set email alerts
|

Results of analyses of fur samples from the San Joaquin Kit Fox and associated soil and water samples from the Naval Petroleum Reserve No. 1, Tupman, California

Abstract: assisted in sample preparation, data preparation, and the framing of hypotheses. Tom O'Farrell provided advice and encouragement. vii ABS'TRACT The purpose of this study was to determine whether analysis of the elemental content of , fur from San Joaquin kit foxes (Vulpes macrotis mutica) and of water and soil from kit fox habitats could be used to make inferences concerning the cause of an observed decline in the kit fox population on Naval Petroleum Reserve No. 1 (NPR-1). Fur samples that had been collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Associating evidence with links in a network model can illustrate mechanistic causal relationships within the body of evidence. When causation is unclear because the evidence is not concordant, reorganizing the model to illustrate a better understanding of causal relationships can make the evidence concordant or show what additional evidence is needed (Suter and O'Farrell 2008; USEPA 2010; Norton and Schofield 2018). A related approach is the weighing of evidence for adverse outcome pathways, which are conceptual models of chemically agnostic mechanisms of toxic action (OECD 2016).…”
Section: Integrating Woe and Sr Practicesmentioning
confidence: 99%
“…Associating evidence with links in a network model can illustrate mechanistic causal relationships within the body of evidence. When causation is unclear because the evidence is not concordant, reorganizing the model to illustrate a better understanding of causal relationships can make the evidence concordant or show what additional evidence is needed (Suter and O'Farrell 2008; USEPA 2010; Norton and Schofield 2018). A related approach is the weighing of evidence for adverse outcome pathways, which are conceptual models of chemically agnostic mechanisms of toxic action (OECD 2016).…”
Section: Integrating Woe and Sr Practicesmentioning
confidence: 99%
“…In the limited studies available of ecological impacts of oil field activity in California, there are a few documented cases of giant kangaroo rats, blunt-nosed leopard lizards and San Joaquin kit foxes drowning in accidental spills of oil and oil-laden wastewater (Kato and O'Farrell, 1986;O'Farrell and Kato, 1987). Suter et al (1992) examined the elemental content of fur samples from San Joaquin Kit Foxes inhabiting two oil fields (one active, one inactive), and two control areas. They found that foxes on the developed sites had elevated levels of a number of elements which may be attributable to oil field materials.…”
Section: Discharges Of Wastewater and Stimulation Fluids Can Affect Wildlife And Vegetationmentioning
confidence: 99%